(untitled) (Eurasian Research Bulletin, 2022)
This paper describes experimental methods for the separation of nickel ions from the adsorbent using dimethylglyoxime in the regeneration of adsorbents.A universal buffer solution with pH = 8.0 was used to study the dependence of the composition of buffer solutions on the main reaction Ni2+-Rreagent) components